Experiences of frontline nurses caring COVID-19 patients − A thematic analysis - Leena Sequira; Shalini Ganesh Nayak; Shobha Nayak (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The COVID-19 pandemic exerts a considerable impact on the healthcare setting and healthcare provider's personal and social life. Adjusting to an entirely new working environment may have added challenges for the nurses without having infectious disease expertise. The study aimed to understand and describe the experiences of nurses taking care of COVID-19 patients in a tertiary care Hospital. MATERIALS AND METHODS: The study was conducted in a tertiary care multispecialty hospital of Udupi District, Karnataka, India. A qualitative research approach with thematic analysis was used in this study. The inclusion criteria were staff nurses caring for COVID-19 patients for a minimum of 1 week. Samples were selected by purposive sampling technique, and the data saturation was achieved with 12 participants. Data were collected through in-depth, face-to-face interviews directed by a semi-structured interview guide. The interviews were audio-recorded and then transcribed verbatim. Thematic analysis derived from participant's responses. Data collection and data analysis were performed simultaneously. The data were analyzed using Kiger and Vapiro's six-step process of thematic analysis of qualitative data. RESULTS: Ten subthemes were grouped from the three major themes under "working in COVID-19 facility: A "challenging experience", "adaptive coping strategies", and "support during a pandemic" emerged based on the experiences of staff nurses working with the COVID-19 patients. CONCLUSION: Staff nurses in this study had challenging experiences attributed to several factors at the outbreak of the COVID-19 pandemic. Meanwhile, strategies to confront the difficulties were adopted by them to improve their well-being.